2016
DOI: 10.1016/j.bbrc.2015.12.027
|View full text |Cite
|
Sign up to set email alerts
|

Nanoformulated copper/zinc superoxide dismutase attenuates vascular cell activation and aortic inflammation in obesity

Abstract: Our data show that nanoSOD is very effective in delivering active SOD to ECs and in reducing EC oxidative stress. Our data also demonstrate that nanoSOD will be a useful tool to reduce vascular cell activation in VAT and aorta in obesity which, in turn, can protect against obesity-associated CVD, in particular, hypertension.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…We previously reported that Nano preferentially delivers SOD1 to endothelial cells compared to native unmodified SOD1 [29]. To determine whether Nano effectively delivers SOD1 to myocytes, we performed in vitro studies in cultured C2C12 myocytes.…”
Section: Resultsmentioning
confidence: 99%
“…We previously reported that Nano preferentially delivers SOD1 to endothelial cells compared to native unmodified SOD1 [29]. To determine whether Nano effectively delivers SOD1 to myocytes, we performed in vitro studies in cultured C2C12 myocytes.…”
Section: Resultsmentioning
confidence: 99%
“…The antioxidant effect of SOD at the cardiovascular level has also been demonstrated in human aortic endothelial cells (HAEC), in which nano-SOD decreased linoleic acid-induced oxidative stress, as demonstrated by the in vivo assessment of nano-SOD in vascular-cell activation in a mouse model of diet-induced obesity. Nano-SOD caused a significant decrease in vascular-cell activation in the thoracic aorta, in heart inflammation and in MMP expression in the aorta and ventricles [ 191 ].…”
Section: Sod As a Pharmacological Agentmentioning
confidence: 99%
“…In particular, Zn supplementation significantly increased GPx activity through modulation of Se status [ 53 ]. It has also been demonstrated that nanoformulated Cu,Zn-SOD is capable of decreasing adipose tissue [ 54 ] and vascular [ 55 ] inflammation in obese mice.…”
Section: Introductionmentioning
confidence: 99%